Father Presence and Adolescent Attitudes toward Sexual Behavior - Pusparatri, Edita; Rahmawati, Ashri Maulida; Jauhar, Muhamad; Khoirunnisa, Fania Nurul (Journal of Bionursing, 2025)
The presence of fathers in children's lives, especially during adolescence, is one of the protective factors that can prevent children from risky behavior, including negative adolescent attitudes towards sexual behavior. This study aims to measure the relationship between father's presence and adolescents' attitudes towards sexual behavior. The research design used descriptive correlation with a cross sectional approach. The study was conducted at a high school in Kudus Regency in 2024. The research sample was 96 students through purposive sampling technique. The research instrument used the Father Presence Questionnaire (FPQ) and the adolescent attitude towards sexual behavior questionnaire which had been valid and reliable. Data analysis using chi square test. The results showed that the majority of adolescents had a positive attitude towards sexual behavior (56.3%). In addition, the majority of adolescents who had high father presence also showed positive attitudes towards sexual behavior (61.1%). However, there was no significant relationship between father's presence and adolescents' attitude towards sexual behavior (p = 0.276). Father's presence in childcare needs to be increased to achieve a good mental health condition in adolescents. Future research is expected to evaluate interventions that can improve the role of fathers in parenting adolescents.